Split Thickness Skin Grafting With and Without Surgical Removal of Granulation Tissue in Granulating Wounds: A Single Blinded, Randomized Controlled Trial - Sharma, Samit; Pokhrel, Biraj; Rayamajhi, Sangam; Shrestha, Jayan M; Lohani, Ishwor (Journal of Institute of Medicine Nepal, 2021)
Introduction: Split thickness skin graft (STSG) is a commonly carried out procedure in granulating wounds. The graft may be applied directly on the granulation tissue (without scrapping) or it may be applied after complete removal of the granulation tissue (after scrapping). Surgeons are divided on this issue. Methods: A single blinded, randomized, controlled trial was carried out between November 2017 and December 2018 in the Department of Plastic Surgery and Burns, Tribhuvan University Teaching Hospital, Kathmandu, Nepal. The study consisted of 62 patients who were divided into two groups. Group A consisted of patients undergoing removal of granulation tissue and Group B included patients on whom the skin graft was directly applied on the granulation tissue. On the 10th post-operative day, assessment of the graft take was done. Results: There was no statistically significant difference in graft take between group A and group B (p=0.59). The average drop in hemoglobin levels after the surgery was 1.6 gm% in group A and 0.4 gm% in group B and this difference was statistically significant. Also, the drop of serum protein after surgery was 8.6% gm/dl in group A and 1.0 gm/dl in group B and this difference was significant. Conclusion: There was no significant difference in the take of skin graft with or without removal of granulation tissue in our study. However, with lesser blood loss, lesser protein loss and lesser operative time, this study favours skin grafting without the removal of granulation tissue.